Sosialisasi Pengangkatan Anak Dalam Adat Melayu Dalam Perspektif Hukum Islam Dan Positif - Abdullah Sani Kurniadinata; Muhammad Shaleh; Riyan Juliantoro (El-Mujtama: Jurnal Pengabdian Masyarakat, 2021)
This thesis aims to find out how the practice of adopting traditional children, and how the position of children adopted by Langkat Pepadun and Saibatin customs, to find out how to adopt Langkat Pepadun and Saibatin traditional children in a positive and Islamic legal perspective. This research uses field research methods, and is a type of qualitative research. This analytic research is a continuation of descriptive research which aims not only to describe certain characteristics, but also to analyze and explain why and how it happened. The approach used in this study uses an empirical normative approach. The data criteria used were interviews, literature studies, and documentation studies. The adoption of traditional children is carried out if there is a marriage of different ethnic groups and is carried out before the wedding and is carried out openly and in cash, namely by way of deliberation and presenting the parties concerned with the help of local traditional leaders. And the position of the adopted child in the customs is equated with the biological child, in the sense that his care and affection is the same as that of the biological child by not breaking the lineage relationship of the adopted child with his biological parents. The adoption of the traditional children of is done only for someone who comes from outside the tribe in order to get recognition from the ethnic group and so that the Langkat tribe itself does not lose its status in adat as indigenous people. Keywords: Adoption of children